WOMEN IN ELITE POSITIONS IN LISTED CORPORATIONS IN THE PHILIPPINES - Supangco, Vivien T. (Philippine Management Review; Vol 15 (2008), 2009)
This study looks into women’s access to elite positions: women in management and women on the board of directors or in governance. It focuses on the organizational factors that determine women’s access to these top-level positions. One hundred companies listed in the Philippine Stock Exchange comprise the sample. Institutional theory and resource dependence theory inform the hypotheses in this study. Results indicate the interrelationship between women in governance and women in management. They are, however, invariant to organizational age and size and industry sector.
Keywords: women, gender, women in governance, women in management